'Warriors for the Working Day'. Henry V: Integrity, Identity and Dialogue in Public Leadership. (2nd January 2023) - Robinson, Simon; Smith, Jonathan
Abstract: This paper focuses on integrity and organizational leadership through the lens of Shakespeare's Henry V, aiming to contribute to the debate about integrity in public administration. First, it sets out some of the major themes about integrity in public administration. Second, the paper begins to develop these themes, noting a common link between integrity and identity. This sets out a complex view of integrity which is holistic, inter- personal, and focused in critical reflection and learning. This involves shared creativity and positive critical engagement with the different narratives which make up individual, organizational and community identity, and embodies the three modes of responsibility: agency, accountability and creative responsibility, focused in deliberation, narrative development and dialogue. Third, the main body of the paper begins to illustrate this view of integrity through Shakespeare's depiction of Henry V's leadership, focused in critical plural dialogue, expressed in the Crispin's Day speech, and developed in the formation of Henry. Implications of this view for practice are offered throughout this analysis ending with suggestions about how developing such a culture in and beyond public administration.